Atividade antioxidante dos frutos de quatro cultivares de pessegueiro de região subtropical - Santos, Cláudia Mendes dos (2011)
Foods supply not only essential nutrients necessary to life but also bioactive compounds with biological properties, the so-called health-promoters such as: antioxidant, anti-inflammatory and anti-carcinogenic activities. In the latest years, the scientific focus on plants, their composition in terms of antioxidant content and their active role in human welfare, have grown markedly. Antioxidants and the correlation between their occurrence and quality of fruits are widely investigated. In particular, a great deal of efforts has been conducted to identify the plants with high contents of antioxidants which confer benefits to health. In peach (Prunus persica L.), the greatest source of antioxidant capacity is represented by the phenolic compounds, vitamin C and carotenoids. In this way, the purpose of this work was to characterize four cultivars of peach tree (Aurora, Biuti, Diamante and Douradão), coming from the towns of Lavras and Nepomuceno/MG, in relation to the antioxidant capacity and determine the content of the antioxidant compounds related to that activity. The fruits were divided into two groups: without storage and storage for five days at room temperature (25ºC ±0.87 ºC and 69.5% ± 2.35%UR). The contents of vitamin C, carotenoids and phenolic compounds and the antioxidant capacity were determined. The four cultivars proved rich in antioxidant substances but, the intensity of that action was distinct among them. The main contribution to the antioxidant activity of peaches was given by the phenolic compounds which presented the best correlation with the DPPH tests and -carotene/ linoleic acid. Cultivar Biuti presented an increased content of all the analyzed substances and a higher antioxidant activity. It was found that the antioxidant potential of the fruits was not influenced negatively by the storage period.